Pharmacological treatment of multidrug-resistant tuberculosis (MDR-TB) in patients co-infected with HIV and its incidence in Federal District – Brazil (Research, Society and Development, 2022)
People living with HIV (PLHIV) are at greater risk of infection and development of tuberculosis, caused by Mycobacterium tuberculosis. In Brazil, the high mortality rate is identified precisely on the occasion of coinfection and it can actively lead to severe complications. This study aimed to analyze the treatment of multidrug-resistant tuberculosis in patients co-infected with HIV and the incidence of this condition in the Federal District, Brazil. We reviewed the literature via the databases PubMed, Embase, and Biblioteca Virtual em Saúde between September and October of 2021, and selected 15 studies fitting the eligibility criteria. The unified health system provides the first-line treatment and recommends using the Directly Observed Treatment. However, when there is resistance or significant intolerance to first-line drugs, second-line drugs are needed. Drug repositioning may be a promising strategy to improve tuberculosis treatment through new therapeutic options and to overcome these problems. The risk of interactions and their complications in PLHIV in antiretroviral therapy and second-line treatment of tuberculosis is even more concerning, which can result in reduced efficacy or increased toxicity of both treatments. Nevertheless, children show better outcomes among patients in TB/HIV co-infection studies, even after second-line treatment fails. These results demonstrate the complexity and seriousness of co-infection epidemiology, treatment, follow-up, and margin of success. Aggravated by factors such as increasing resistance to M. tuberculosis in Brazil and the world, the challenge of monitoring patients' treatment and keeping their adhesion, and the high rate of adverse effects caused by drugs.